2014
DOI: 10.1016/j.domaniend.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic characterization of uterine histotroph recovered from beef heifers yielding good quality and degenerate day 7 embryos

Abstract: 16The objective was to analyse the proteomic composition of uterine flushes collected from 17 beef heifers on Day 7 post-insemination. Oestrus was synchronised in cross-bred beef heifers 18 using a Controlled Intravaginal Drug Releasing device (CIDR) protocol. Heifers detected in 19 standing oestrus (within 24-48 h post CIDR removal) were inseminated (oestrus=Day 0) with 20 frozen-thawed semen from a single ejaculate of a bull with proven fertility. Heifers from 21 which an embryo was recovered (following slau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 56 publications
(59 reference statements)
1
24
0
Order By: Relevance
“…After collecting the samples and identifying the proteins, it was found that in the degenerate embryo group, it was only one protein which had high expression in comparison with the normal group, and it was S100a4 protein. Consequently increasing the frequency of S100a4 in the degenerative embryo group indicates a negative effect of S100a4 on early embryo development …”
Section: S100 Family and Implantation Of Embryomentioning
confidence: 99%
“…After collecting the samples and identifying the proteins, it was found that in the degenerate embryo group, it was only one protein which had high expression in comparison with the normal group, and it was S100a4 protein. Consequently increasing the frequency of S100a4 in the degenerative embryo group indicates a negative effect of S100a4 on early embryo development …”
Section: S100 Family and Implantation Of Embryomentioning
confidence: 99%
“…It is interesting to note that the majority of studies conducted to understand the global holistic uterine proteome in large animals have been performed in the last 5 years . Cows seem to have been the species of choice in these investigations . The sample most used for the global analysis of the uterine proteome has been based on the uterine fluid or flushings of uterus .…”
Section: Proteomic Profile Of the Uterusmentioning
confidence: 99%
“…Cows seem to have been the species of choice in these investigations . The sample most used for the global analysis of the uterine proteome has been based on the uterine fluid or flushings of uterus . Nearly all these studies are concerned with defining, characterising and identifying the proteins present in the uterine fluid or tissue at different stages of the reproductive cycle or during the early stages of establishment of pregnancy.…”
Section: Proteomic Profile Of the Uterusmentioning
confidence: 99%
“…These invasive methods allow the collection of epithelial and inflammatory cells (CB, CT, UL), luminal secretions (UL) and uterine tissue (EB). The samples obtained can be used to accurately diagnose the uterine status by using a single or combined assessment with cytological smears (Kasimanickam et al, 2004, Pascottini et al, 2015, bacteriological culture (Bonnett et al, 1991a), protein analysis (Beltman et al, 2014), histopathology (Chapwanya et al, 2010), and gene expression (Munoz et al, 2012) These tests are better indicators of uterine health than the subjective non-invasive methods. Here I describe three common approaches with different degrees of invasiveness which I used experimentally.…”
Section: Invasive Uterine Assessmentmentioning
confidence: 99%
“…However, the yield of endometrial cells recovered from uterine fluid is less and this affects subsequent cytological analysis and this is worse than in samples recovered from CB (Kasimanickam et al, 2005b, Barlund et al, 2008, Cocchia et al, 2012. As mentioned before, the composition of UF is a complex mixture of molecules and substances derived from genes expressed in the endometrium or transported from maternal blood (Beltman et al, 2014). The proteome profile of the histotroph has been widely studied in cattle.…”
Section: Collection Of Uterine Fluidmentioning
confidence: 99%